The Application of Hip Rotation Training to Improve Discus Throwing Technique - Ahmad Arifin; Gatot Sukartono; Acep Rohmat Nurhidayat (Journal of Innovative and Creativity, 2025)
This study aims to improve university students’ discus throwing technique through the implementation of hip rotation training based on a biomechanical approach. The main issue addressed is the low quality of hip rotation technique and insufficient throwing distance among students enrolled in athletic practicum courses. The research was conducted at the Physical Education Study Program, Universitas Pamulang, involving 24 second-semester students as research participants. The method employed was Classroom Action Research (CAR), carried out over two cycles, each consisting of planning, action, observation, and reflection stages. The results showed that systematic hip rotation training significantly improved students’ discus throwing techniques. The average throwing distance increased from 13.2 meters in the pre-cycle to 15.1 meters in the first cycle, and further to 17.6 meters in the second cycle. Likewise, the percentage of students demonstrating adequate technique rose markedly from 16.7% (pre-cycle) to 58.3% (Cycle I), and reached 87.5% in Cycle II. Hip rotation training effectively enhanced postural stability, body coordination, and energy transfer efficiency during throwing movements. These findings indicate that hip rotation training is an effective and applicable instructional strategy for improving technical skills in sports, particularly in discus throwing. The biomechanical approach used in this study can serve as a practical learning model for athletics courses in higher education settings. Therefore, integrating hip rotation exercises into physical education curricula is highly recommended to optimize students’ motor skill development.